Penerapan Terapi Menghardik Terhadap penurunan Skor Halusinasi Dengar Pada Pasien Skizofrenia Di RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah: Applications Of Therapeutic Therapy To Decrease Score Of Hearing In Schizoprenic Patients At RSJD Dr. Amino Gondohutomo Central Java Province - Delima Fitri Hapsari; Nanang Khosim Azhari (JURNAL KEPERAWATAN SISTHANA, 2020)
Schizophrenia is a neurological disease that affects the person's perception, thinking, language, emotional, and social behavior of a person. One of the symptoms of schizophrenia is hallucinations. Hallucination is a lost person's ability in distinguishing the stimulation from the outside or from within. The results of a survey obtained from RSJD Dr. Amino Gndohutomo central java province of hallucinations is the most common problem that is reaching 2.398 inhabitants. One of the efforts to deal with the hallucination is scolded. Scolded is an effort that can be done to control his hallucinations by way of rejecting the hallucinations that arise. The purpose of this case study to find out the decrease in the score of the hallucinations of schizophrenia patients have heard before and after the therapy done and scolded. This research uses descriptive analysis type by using the method of approach to the case studies. The subjects used are 2 subjects with impaired auditory hallucinations. The results showed there is a difference between before and after the therapy is carried out on the subject I from 42 became 37, and subject II from 39 became 30. It can be concluded that the result of this study indicate that scolded therapy able to reduce the level of hallucinations in schizophreia patients, therefore if done with a routine then the level of hallucination will come down and help the healing process.